FAKTOR YANG MEMPENGARUHI STRATEGI BERTAHAN HIDUP PEREMPUAN PULAU DI DESA GEDUGAN, PULAU GILIGENTING, KABUPATEN SUMENEP - Ismi Aulil Wardani; Keppi Sukesi; Reza Safitri (Universitas Sebelas Maret, 2019)
Income is one of the factors that influence Island women to carry out a survival strategy. Not only that, there are still other factors that influence. These factors are collected in household asset capital, each of which is interrelated and there is also a factor that is most dominating among others. This study aims to identify and analyze the factors that influence the survival strategy in Gedugan Village, Giligenting Island and analyze the relationship between the factors that influence the survival strategy of island women. The method used is quantitative analysis by distributing questionnaires (Likert scale), observation and interviews. The sampling method used was random sampling with Slovin. The variables used in this study are financial capital, social capital, natural capital, physical capital and human capital, while the analytical method used is factor analysis and multiple linear regression analysis. The results showed that the most dominant and most influential factor on the survival strategy of Pulau Perempuan was financial capital.